2004
DOI: 10.1037/0735-7044.118.4.869
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Dopamine Efflux in the Rat Nucleus Accumbens During Successive Negative Contrast.

Abstract: Rats shifted from 4% to 32% sucrose displayed successive negative contrast by initiating significantly fewer bouts of licking than control rats maintained on 4% sucrose. No significant increase in dopamine (DA) efflux in the nucleus accumbens (NAc) was observed during consumption of 4% sucrose by rats shifted from 32%. In contrast, consumption of 4% sucrose by control rats was accompanied by a significant increase in DA efflux in the NAc, which remained elevated 10 min postconsumption. These data are consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 27 publications
2
40
0
Order By: Relevance
“…With experimenter-delivered drug, we have found that avoidance of a saccharin cue following a single saccharin-morphine pairing is accompanied by a full blunting of the accumbens dopamine response to the saccharin reward cue [69]. While negative contrast (reward devaluation) may contribute to this finding with dopamine [70], this blunting also could be explained by the onset of cue-induced craving and/ or withdrawal because accumbens dopamine levels also are blunted following the onset of naltrexone-induced withdrawal [71]. Second, using experimenter-delivered drug, we have found large individual differences whereby some rats are more likely to avoid intake of the drug-associated taste cue than are others and greater avoidance of the taste cue is associated with greater cue-induced elevation of circulating corticosterone [72].…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 97%
“…With experimenter-delivered drug, we have found that avoidance of a saccharin cue following a single saccharin-morphine pairing is accompanied by a full blunting of the accumbens dopamine response to the saccharin reward cue [69]. While negative contrast (reward devaluation) may contribute to this finding with dopamine [70], this blunting also could be explained by the onset of cue-induced craving and/ or withdrawal because accumbens dopamine levels also are blunted following the onset of naltrexone-induced withdrawal [71]. Second, using experimenter-delivered drug, we have found large individual differences whereby some rats are more likely to avoid intake of the drug-associated taste cue than are others and greater avoidance of the taste cue is associated with greater cue-induced elevation of circulating corticosterone [72].…”
Section: The Model: Experimenter Delivered Drugmentioning
confidence: 97%
“…The effects of NAc injections of raclopride on flavor-nutrient learning were not investigated given the lack of effect obtained with systemic injections of the D2 antagonist. The NAc is a site at which sweet solutions in the mouth stimulate dopamine efflux (e.g., [12,16,17]). Whether IG sugar infusions also promote dopamine release in the NAc is not known.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleus accumbens shell (NAcS) is a site in which sweet taste stimulates dopamine efflux (e.g., [12,16]), and where dopamine antagonists in the NAcS suppress lithium chloride-conditioned saccharin aversions [14]. Therefore, the present experiment examined whether dopamine D1 (SCH23390) or D2 (raclopride) antagonists administered bilaterally into the NAcS would dose-dependently alter the acquisition and/or expression of fructose-conditioned flavor-flavor preferences.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, rats treated with an ED regimen of D-amph failed to display successive positive contrast when shifted from 4 to 32% sucrose (Vacca and Phillips, 2005), a finding that parallels the enhancement of successive negative contrast observed in rats withdrawn from the same drug treatment . Genn et al (2004) have recently shown that DA efflux in the NAc was significantly attenuated when rats unexpectedly experience a reward of a lesser value in a negative contrast paradigm. Together, these data indicate that short-term abstinence from psychostimulants has a significant effect on the motivation to respond for natural rewards.…”
Section: Discussionmentioning
confidence: 99%